The simplest variable to eliminate is y: 8y and 2y differ by factor of 4.Multiply the second equation by -4 and add to the first:
(7x+8y) + (-4)*(3x+2y) = 4 + (-4)*6,7x + 8y - 12x - 8y = 4 - 24,-5x = -20,x = 4.
Now substitute x=4 to the, say, second equation and obtain
3*4 + 2y = 6,2y = 6 - 12 = -6,y = -3.
The answer is: x=4, y=-3.
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?